Targeted delivery of CRISPR-Cas9 ribonucleoprotein into arthropod ovaries for heritable germline gene editing - Duverney Chaverra-Rodriguez (Nature Portfolio, 2018)
Delivery of Cas9 ribonucleoprotein complexes can be done via microinjection into eggs, though this is a technically challenging procedure. Here the authors demonstrate ReMOT Control, delivery of RNPs to the mosquito germline by tagging with peptide derived from yolk protein 1.